Spatial analysis of built-up land development in 1995 and 2025 based on slope level in Ternate City, Indonesia - Rifai, Ahmat; Rakuasa, Heinrich; Latue, Philia C; Halim, Halim; Rajani, La Mbeli (Jurnal Geosains West Science, 2025)
Ternate City in North Maluku, Indonesia, is experiencing rapid population growth and residential land development, with diverse topography and slopes that affect the expansion of built-up land. This study analyzed the development of built-up land in 1995 and 2025 based on slope levels using Landsat imagery and Digital Elevation Model (DEM) data. The results showed that built-up land expanded rapidly in the 8-25% slope zone (an increase of 96.8-372%) and the >25% zone (+206.5%), indicating that development pressure pushed urbanization into topographically difficult areas. Greenland conversion (903.78 ha less) also affected the environmental balance, while water bodies remained stable (67.58 ha). The dominance of steep slopes >40% (3,013.36 ha) is a major challenge for sustainable development. These findings emphasize the need for a spatial approach based on integrated geomorphological analysis, particularly landslide risk mitigation in steep slope zones, while meeting settlement needs